Bridging Three Gaps in Biodegradable Plastics: Misconceptions and Truths About Biodegradation - Choe, Shinhyeong; Kim, Yujin; Won, Yejin; Myung, Jaewook (Frontiers in Chemistry, 2021)
In the wake of plastic pollution increasing around the world, biodegradable plastics are one of the fastest-growing segments within the global plastics market. The biodegradation of these plastics depends on diverse factors including, but not limited to, the physicochemical structure of the materials, environmental conditions, and the microbial populations involved in the biodegradation. Although laboratory-based biodegradation tests simulate natural processes, they cannot precisely mimic the natural biodegradation of biodegradable plastics due to the disparity of several factors. In addition, the biodegradation levels claimed and/or reported by individuals and studies in different environments vary to a great extent. Biodegradable plastics are considered a sustainable alternative to fossil-based conventional plastics and are being promoted as an eco-friendlier choice for consumers. However, biodegradable plastics might not be as biodegradable as commonly believed, particularly in natural environments. This mini-review aims to bridge the following three gaps in biodegradable plastics by elucidating the common misconceptions and truths about biodegradation: i) the gaps among their reported biodegradation level of biodegradable plastics; ii) the gaps between the biodegradation conditions in the controlled laboratory system and in the natural environment; and iii) the gaps between public perception and the actual environmental fate of biodegradable products. These gaps are critically reviewed with feasible solutions. This work will ease the assessment of biodegradable plastics and provide sound communication on corresponding claims–a prerequisite for successful market performance.